One for All and All for One: Intra-Organizational Dynamics in Humanitarian Action - Webster, Mackinnon; Walker, Peter (Tufts Archival Research Center, 2005)
A significant proportion of humanitarian assistance is now delivered by NGOs which have in effect become federated trans-national organizations, alliances of members from different countries, all seeking to provide assistance in times of crisis. This report describes research carried out to better understand how these transnational bodies organize their membership, deliver and accountability systems in times of crisis.